PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA KEPADA LOYALITAS PELANGGAN PADA EXCELSO CAFE DI KOTA PONTIANAK - admin, YULIANA B11111099 (Jurnal Manajemen Update, 2016)
ABSTRACT This research aims to analyze the influence of experiential marketing on customers loyalty with customers satisfaction as an intervening variabel of Excelso Cafe Pontianak. This research consists of dependent variable which is customer loyalty and independent variables which are experiential marketing consists of sense, feel, think, act and relate. The population of the research is the customer of Excelso Cafe Pontianak who have been visiting at least twice with a sample of 100 respondents. The sampling technique that is used in this research is purposive sampling and then the data was processed by path analysis. The results of analysis for the first model show that simultaneously sense, feel, think, act and relate have a significant effect on customers satisfaction. Partially feel, act and relate have a positive and significant effect on customers satisfaction while sense and think have no effect. Predictive capability of the five variabels on customers satisfaction is 67,3% while the remaining 32,7% was influenced by other factors not included in the research model. The results of analysis for the second model show that simultaneously sense, feel, think, act, relate and customers satisfaction have a significant effect on customers loyalty. Partially feel, think and customers satisfaction have a positive and significant effect on customers loyalty while sense, act and relate have no effect. Predictive capability of the six variabels on customers loyalty is 77,6% while the remaining 22,4% was influenced by other factors not included in the research model. Keywords: sense, feel, think, act, relate, customers satisfaction and customers loyalty